IoT (Internet of Things) Technologies And Their Applications In Everyday Life - Sultonova, Diloromxon Qo'ldashevna (TLEP – International Journal of Multidiscipline, 2025)
The Internet of Things (IoT) represents a paradigm shift in human-computer interaction, weaving a network of interconnected physical devices into the fabric of everyday life. This paper investigates the applications of IoT technologies in quotidian routines and examines the corresponding user perceptions regarding their benefits and challenges. The primary objective is to map the landscape of IoT adoption across key domains—such as smart homes, wearable technology, and personal transportation—while critically evaluating the socio-technical tensions that arise, particularly concerning data privacy and security. Employing a mixed-methods approach, this study synthesizes existing literature and analyzes quantitative data from a cross-sectional survey of 500 adult users. The results indicate that while convenience and efficiency are the primary drivers of IoT adoption, these benefits are significantly counterweighed by profound user concerns about data security and personal privacy, especially for devices equipped with audio-visual sensors. The findings reveal a significant ’privacy paradox,’ where users continue to adopt technologies despite harboring deep-seated anxieties. This research concludes that the future trajectory of IoT integration is contingent upon fostering user trust through transparent data policies, robust security frameworks, and a human-centric design philosophy. It underscores the urgent need for collaboration between technologists, policymakers, and end-users to navigate the ethical complexities of a pervasively connected world.